(untitled) (Colombia Medica, 2019)
Aim: To assess the risk of tuberculosis (infection and disease) in children less than 15 years’ old who are household contacts of pulmonary tuberculosis patients in three Colombian cities (Medellín, Cali, and Popayán). Methods: A cohort of 1,040 children household contacts of 380 adults with smear-positive pulmonary tuberculosis was followed up for 24 months. Study period 2005-2009. Results: Tuberculin skin test was positive (≥10 mm) in 43.7% (95% CI: 39.2-48.2). Tuberculin skin test positivity was associated with age 10-14 years (Prevalence Ratio -PR= 1.43, 95% CI: 1.1-1.9), having a BCG vaccine scar (PR= 1.52, 95% CI: 1.1-2.1), underweight, closer proximity to the index case and exposure time >3 months. The annual risk of infection (tuberculin skin test induration increase of 6 mm or more per year) was 17% (95% CI: 11.8-22.2) and was associated with a bacillary load of the adult index case (Relative Risk -RR= 2.12, 95% CI: 1.0-4.3). The incidence rate of active tuberculosis was 12.4 cases per 1,000 persons-year. Children <5 years without BCG vaccine scar had a greater risk of developing active disease (Hazard Ratio -HR= 6.00, 95% CI: 1.3-28.3) than those with scar (HR= 1.33, 95% CI: 0.5-3.4). The risk of developing active tuberculosis augmented along with the increase from initial tuberculin skin test (tuberculin skin test 5-9 mm HR= 8.55, 95% CI: 2.5-29.2; tuberculin skin test ≥10 mm HR= 8.16, 95% CI: 2.0-32.9). Conclusions: There is a need for prompt interruption of adult-to-children tuberculosis transmission within households. Conducting proper contact investigation and offering chemoprophylaxis to infected children could reduce tuberculosis transmission.